2011
DOI: 10.1103/physreva.83.021804
|View full text |Cite
|
Sign up to set email alerts
|

Scaling laws for precision in quantum interferometry and the bifurcation landscape of the optimal state

Abstract: Phase precision in optimal 2-channel quantum interferometry is studied in the limit of large photon number N 1, for losses occurring in either one or both channels. For losses in one channel an optimal state undergoes an intriguing sequence of local bifurcations as the losses or the number of photons increase. We further show that fixing the loss paramater determines a scale for quantum metrology -a crossover value of the photon number Nc beyond which the supra-classical precision is progressively lost. For la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
181
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(191 citation statements)
references
References 18 publications
10
181
0
Order By: Relevance
“…Is it then really possible to outperform classical strategies in practical phase sensing [100]? Surprisingly, it has been shown that asymptotically it is possible to do so only by a constant factor [101,102]: for any nonzero loss, for sufficiently high number of photons N the scaling of the optimal phase sensing is proportional to the scaling of the shot noise ∝ N −1/2 . While this means that quantum approaches are useful in highly controlled environments [102] (such as for gravitational wave detection [1]), they only allow for very small enhancements in free-space target acquisition [102].…”
Section: Quantum Metrology With Noisementioning
confidence: 99%
See 1 more Smart Citation
“…Is it then really possible to outperform classical strategies in practical phase sensing [100]? Surprisingly, it has been shown that asymptotically it is possible to do so only by a constant factor [101,102]: for any nonzero loss, for sufficiently high number of photons N the scaling of the optimal phase sensing is proportional to the scaling of the shot noise ∝ N −1/2 . While this means that quantum approaches are useful in highly controlled environments [102] (such as for gravitational wave detection [1]), they only allow for very small enhancements in free-space target acquisition [102].…”
Section: Quantum Metrology With Noisementioning
confidence: 99%
“…Surprisingly, it has been shown that asymptotically it is possible to do so only by a constant factor [101,102]: for any nonzero loss, for sufficiently high number of photons N the scaling of the optimal phase sensing is proportional to the scaling of the shot noise ∝ N −1/2 . While this means that quantum approaches are useful in highly controlled environments [102] (such as for gravitational wave detection [1]), they only allow for very small enhancements in free-space target acquisition [102]. Nonetheless, the shot noise can be beaten [103] and the optimal states to do so in the presence of loss have been calculated numerically using various optimization techniques for fixed number of input photons [104,105] and for photon-number detection [106].…”
Section: Quantum Metrology With Noisementioning
confidence: 99%
“…2 Moreover, loss will be present in any practical scenario, including absorbance in measured samples and non-unit efficiency detectors. Consequently, revised scaling laws of precision with photon flux have been derived, 17 along with optimised superposition states of fixed photon number, numerically for small photon number 18,19 and analytically for large. 17 Here, we demonstrate the underpinning principles of a practical -loss-tolerant-scheme for sub-shot-noise interferometry, illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, revised scaling laws of precision with photon flux have been derived, 17 along with optimised superposition states of fixed photon number, numerically for small photon number 18,19 and analytically for large. 17 Here, we demonstrate the underpinning principles of a practical -loss-tolerant-scheme for sub-shot-noise interferometry, illustrated in Figure 1. This scheme is designed to use the full fourmode multi-photon state naturally occurring in a non-linear optical process known as type-II spontaneous parametric downconversion (SPDC), which generates a coherent superposition of correlated photon-number states.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior has been argued to be generic to all Heisenberg scaling schemes (see Refs. [20][21][22][23]), so it is not surprising that we also find this behavior here as well. We also showed that the von Neumann measurement interaction also has the phase accumulation effect, provided we prepared the meter states in momentum eigenstates.…”
Section: Discussionmentioning
confidence: 61%